GPR55 is a cannabinoid receptor that increases intracellular calcium and inhibits M current - Lauckner, Jane E; Jensen, Jill B; Chen, Huei-Ying; Lu, Hui-Chen; Hille, Bertil; Mackie, Ken (Proceedings of the National Academy of Sciences - PNAS, 2008)
The CB(1) cannabinoid receptor mediates many of the psychoactive effects of Delta(9)THC, the principal active component of cannabis. However, ample evidence suggests that additional non-CB(1)/CB(2) receptors may contribute to the behavioral, vascular, and immunological actions of Delta(9)THC and endogenous cannabinoids. Here, we provide further evidence that GPR55, a G protein-coupled receptor, is a cannabinoid receptor. GPR55 is highly expressed in large dorsal root ganglion neurons and, upon activation by various cannabinoids (Delta(9)THC, the anandamide analog methanandamide, and JWH015) increases intracellular calcium in these neurons. Examination of its signaling pathway in HEK293 cells transiently expressing GPR55 found the calcium increase to involve G(q), G(12), RhoA, actin, phospholipase C, and calcium release from IP(3)R-gated stores. GPR55 activation also inhibits M current. These results establish GPR55 as a cannabinoid receptor with signaling distinct from CB(1) and CB(2).